2019
DOI: 10.1590/1807-3107bor-2019.vol33.0034
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine gene variability and plasma levels in patients with chronic periodontitis -a case-control study

Abstract: Petra BORILOVA LINHARTOVA (a) Julius JANOS (a) Hana POSKEROVA (a) Denisa KAVRIKOVA (a) Antonin FASSMANN (a) Ladislav DUSEK (b) Lydie IZAKOVICOVA HOLLA (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Leptin is known as an important player in metabolic control, alongside with reproduction and neuroendocrine signaling [ 22 ]. As a relationship between metabolic syndrome, obesity, and diabetes with periodontal disease is well documented in literature, the role of LEP has been repeatedly investigated in this context [ 23 25 ]. While one case-control study did not find an association between LEP and periodontitis [ 23 ], another study found positive correlations between LEP and worse periodontal parameters [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin is known as an important player in metabolic control, alongside with reproduction and neuroendocrine signaling [ 22 ]. As a relationship between metabolic syndrome, obesity, and diabetes with periodontal disease is well documented in literature, the role of LEP has been repeatedly investigated in this context [ 23 25 ]. While one case-control study did not find an association between LEP and periodontitis [ 23 ], another study found positive correlations between LEP and worse periodontal parameters [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a relationship between metabolic syndrome, obesity, and diabetes with periodontal disease is well documented in literature, the role of LEP has been repeatedly investigated in this context [ 23 25 ]. While one case-control study did not find an association between LEP and periodontitis [ 23 ], another study found positive correlations between LEP and worse periodontal parameters [ 24 ]. Considering that, the findings of a prospective observational study, which indicate an association between obesity and periodontitis in individuals with DS, appear of particular interest [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria of the study were as follows: Participants were aged between 18 and 60 years old, were generally healthy, non-smoking, and none had undergone periodontal therapy and/or antibiotic therapy in the past 6 months [ 13 ]. Patients with systemic diseases, such as diabetes mellitus, rheumatoid arthritis, and cancer, pregnant or breastfeeding women were excluded [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also in obese T2DM condition elevated ROS weakens body’s antioxidant defense that induce oxidative damage to tissues, especially the vascular endothelium also contributing to endothelium dysfunction. 117 Endothelial dysfunction caused due to aforementioned condition induce hypertension and vascular injury as it decrease NO production, hence vascular tonicity disrupts. 118 Dyslipidemia in T2DM obese individual accelerates the development of atherosclerotic plaques within the arteries.…”
Section: Obesity and Diabetesmentioning
confidence: 99%